Phytochemical screening, proximate and elemental analysis of Citrus sinensis peels (l.) Osbeck - PO Osarumwense; LO Okunrobo; EG Uwumarongie-Ilori (Journal of Applied Sciences and Environmental Management)
Citrus sinensis was screened for its phytochemical composition and was evaluated for the proximate and elemental analysis. The phytochemical analysis indicated the presence of reducing sugar, saponins, cardiac glycosides, tannins and flavonoids. The elemental analysis indicated the presence of the following mineral elements in various concentrations: Zn, Cu, Mg, and Mn, while Cd and Ni were less than 0.001 and 0.05 respectively, while Cr was about 0.01 in concentration. Proximate analysis also shows that it has a high nutritional value such as carbohydrate, fibre, Ash, fat and protein. These results recommended the consumption of these peels of desired physiochemical properties as sources of food fibres or low-calorie bulk ingredients in food applications requiring oil and moisture retention.